2007
DOI: 10.1002/rcm.2963
|View full text |Cite
|
Sign up to set email alerts
|

Electron capture atmospheric pressure photoionization mass spectrometry: analysis of fullerenes, perfluorinated compounds, and pentafluorobenzyl derivatives

Abstract: An electron capture (EC) ionization mechanism has been found to be highly efficient in negative-ion atmospheric pressure photoionization (APPI) for the analysis of compounds with positive electron affinity (EA). Using negative-ion APPI, we first report the sensitive detection of natural electrophores with limited polarity, such as fullerenes and perfluorinated compounds, by mass spectrometry (MS). Using direct infusion on a quadrupole time-of-flight (QTOF) mass spectrometer, the limits of detection (LODs) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 64 publications
3
37
0
Order By: Relevance
“…Figure 1 demonstrates a NI-DART spectrum of ϳ100 pL PFK in toluene. Compared with the previously reported NI-APPI spectrum of ϳ667 fL PFK in toluene [25], NI-DART was ϳ100 times less sensitive than NI-APPI. Furthermore, the NI-DART spectrum of PFK was more like a NICI spectrum of PFK where an even number of fluorines was easily found for the high m/z ions, while the NI-APPI spectrum of PFK was more like an electron ionization (EI) spectrum of PFK where mostly an odd number of fluorines were found for any ions.…”
Section: Analysis Of Aliphatic Perfluorocarbons (Pfcs)mentioning
confidence: 59%
See 4 more Smart Citations
“…Figure 1 demonstrates a NI-DART spectrum of ϳ100 pL PFK in toluene. Compared with the previously reported NI-APPI spectrum of ϳ667 fL PFK in toluene [25], NI-DART was ϳ100 times less sensitive than NI-APPI. Furthermore, the NI-DART spectrum of PFK was more like a NICI spectrum of PFK where an even number of fluorines was easily found for the high m/z ions, while the NI-APPI spectrum of PFK was more like an electron ionization (EI) spectrum of PFK where mostly an odd number of fluorines were found for any ions.…”
Section: Analysis Of Aliphatic Perfluorocarbons (Pfcs)mentioning
confidence: 59%
“…At the same time, they also possess positive EAs. Our previous study [25] demonstrated that NI-APPI was efficient in the ionization of aliphatic PFCs. Dominant [M -F] Ϫ ions were observed, which was attributed to an EC mechanism for the formation of M Ϫ· ions, and thereafter instant in-source decomposition of the M Ϫ· ions for the formation of [M -F] Ϫ ions.…”
Section: Analysis Of Aliphatic Perfluorocarbons (Pfcs)mentioning
confidence: 98%
See 3 more Smart Citations